2022
DOI: 10.36312/jolls.v2i2.759
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Aspects of Pronunciation Errors Produced by ELE Students in Classroom Settings

Abstract: Pronunciation plays important roles in making the intelligibility of a speech. In pronunciation, speech and gesture production are interrelated and coordinated. Not all language learners can pronounce English words well. Learners make errors while speaking English. It make them not confident to pronounce other English words. Therefore, this study aims to identify students’ segmental aspects of pronunciation errors in classroom setting. This study is categorized as qualitative study to understand phenomena usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 15 publications
(20 reference statements)
2
13
0
Order By: Relevance
“…The statement that YouTube songs can correct English words. Songs on YouTube are equipped with lyrics, pictures and sound which means they can be played many times until students can understand what the song is about and know how to pronounce the words with an English accent (Buana & Irawan, 2021;Nugraha et al, 2022). The teacher also uses group discussion techniques to learn English song lyrics from YouTube.…”
Section: Discussionmentioning
confidence: 99%
“…The statement that YouTube songs can correct English words. Songs on YouTube are equipped with lyrics, pictures and sound which means they can be played many times until students can understand what the song is about and know how to pronounce the words with an English accent (Buana & Irawan, 2021;Nugraha et al, 2022). The teacher also uses group discussion techniques to learn English song lyrics from YouTube.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study indicated that the problem they faced was the students speak a little and often use Vietnamese in the classroom. This study also demonstrated the students speaking performance was influenced by several factors, including their thematic knowledge, ability in listening (Jupri et al, 2022), time preparation, and feedback given by teachers during the learning process (Nugraha et al, 2022). Ariyanti (2016) investigated what factors affected EFL students' speaking performance and focuses on psychological factors using qualitative methods.…”
Section: Introductionmentioning
confidence: 88%
“…Teachers provide students with rich and varied contexts that can improve vocabulary acquisition . By learning new vocabulary in meaningful contexts, students can better understand and retain new words (Nugraha et al, 2022;Buana & Irawan, 2021). For example, if students are learning the vocabulary related to food, they can be taken to a local market or a restaurant where they can see, touch and taste different types of food items.…”
Section: The Teaching Methodology Used By the Teachermentioning
confidence: 99%
“…This need is particularly pronounced in the context of English as an international language (EIL), where pronunciation assumes a pivotal role. The key aspects of pronunciation that hold utmost significance in this context include the correct articulation of certain consonants, the simplification of complex consonant clusters, discrimination of vowel length, and the proper emphasis on syllables and words (Nugraha et al 2022;Yeldham & Choy, 2022). These elements collectively contribute to the intelligibility of speech and serve as crucial preventative measures against problematic pronunciation, ensuring that communication remains clear and effective.…”
mentioning
confidence: 99%
“…Language learners are expected to acquire proficiency in three primary types of diphthongs, namely Diphthong /eɪ/, Diphthong /əʊ/, Diphthong /aɪ/, Diphthong /aʊ/, Diphthong /ɔɪ/, Diphthong /ɪə/, Diphthong /ɛə/, and Diphthong /ʊə/, as outlined by Dyah (2020). The /eɪ/ diphthong, known as a front cover diphthong, initiates with the tongue in the /e/ vowel position, a front vowel slightly below the mid-close position, moving towards the /ɪ/ position, just above mid-close, though the final position may not always be fully reached, with the lips initially open and gradually closing (Dyah, 2020;Nugraha et al, 2022). Examples include words like "raid /reɪd/", "pain /peɪn/", "fail /feɪl/", and "sale /seɪl/".…”
mentioning
confidence: 99%